2017
DOI: 10.1016/j.biortech.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of nitrobenzene and concomitant electricity production by single-chamber microbial fuel cells with activated carbon air-cathode

Abstract: Single-chamber microbial fuel cells (S-MFCs) with bio-anodes and activated carbon (AC) air-cathodes showed high nitrobenzene (NB) tolerance and NB removal with concomitant electricity production. The maximum power over 25Wm could be obtained when S-MFCs were operated in the NB loading range of 1.2-6.2molmd, and stable electricity production over 13.7Wm could be produced in a NB loading range of 1.2-14.7molmd. The present S-MFCs exhibited high NB removal performance with NB removal efficiency over 97% even when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 35 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…A nitrobenzene elimination over 97% was obtained even when the nitrobenzene-loading rate was reached 17.2mol m -3 d -1 . The potential product of nitrobenzene reduction such as aniline can be eliminated efficiently [157]. Xie et al [158] combined a membraneless air-cathode SC-MFC with CW for finding a possible treatment with good nitrobenzene removal efficiency.…”
Section: Nitrobenzenementioning
confidence: 99%
“…A nitrobenzene elimination over 97% was obtained even when the nitrobenzene-loading rate was reached 17.2mol m -3 d -1 . The potential product of nitrobenzene reduction such as aniline can be eliminated efficiently [157]. Xie et al [158] combined a membraneless air-cathode SC-MFC with CW for finding a possible treatment with good nitrobenzene removal efficiency.…”
Section: Nitrobenzenementioning
confidence: 99%
“…Alcohol-powered MFCs were the second dominant community members [37]. The A2 sequence type was 99% similar to uncultured Pseudomonas sp., which have been proven to self-produce phenazine-based mediators in the anodes of MFCs to improve electricity generation [38]. Furthermore, Pham et al demonstrated that metabolites produced by Pseudomonas sp.…”
Section: The Anode Microbial Communitymentioning
confidence: 99%
“…One of the unique advantages of MFCs is the use of different types of waste as feedstock for microbes, whereby contaminants are broken down for the production of electricity [22,23]. So far, a wide range of waste materials have been used as substrates, e.g., waste from the brewery, dairy or oil refinery industries, food processing wastewater and domestic wastewater, among others [24][25][26].…”
Section: Introductionmentioning
confidence: 99%